Staphylococcus aureus: Resistance patterns to antimicrobials and penicillinase among strains isolated from apparently healthy lactating cows - Cavalieri De Araújo, Maria Lúcia [UNESP]; Andrioli, João Luciano (My University, 1996)
Ninety-two strains of Staphylococcus aureus isolated from the nasal fossa and udder skin of apparently healthy lactating cows were analyzed for resistance to antibiotics and production of penicillinase. The results showed a greater frequency of resistance patterns to penicillin and ampicillin. All strains were sensitive to oxacyllin and gentamicin. The most frequent Barber and Burston model was SSSS (60.90%), followed by RSSS (18.50%). With respect to the production of penicillinase, although the Lucas method indicated a larger number of positive samples, we suggest the use of the Haight and Finland method due to a greater consistency of data obtained with it.
Keywords: antibiogram; penicillinase; Staphylococcus aureus